Responsabilidad patrimonial del Estado y función legislativa. Sobre la responsabilidad del Estado por el indebido trámite de iniciativas legislativas de carácter popular. (2018)
This article analyzes if it is appropriate to attribute patrimonial responsibility to the estate, under the imputation title of the service failure, when the Parliament in exercise of its duties breaks the constitutional norms, rules or principles that regulate the procedure to rule a legislative initiative of a popular nature. A bibliographic and jurisprudential review of the state of the art was made and cases were taken as a reference for analysis, establishing that the responsibility of the legislating estate can be predicated, due to a failure in the legislative function that occurred within the process of an initiative of popular origin. Although the proposed typology of responsibility must be developed in depth, the article finds sufficient arguments to indicate the existence of a type of responsibility of the legislating State that has not yet been analyzed.